1997
DOI: 10.1084/jem.185.8.1423
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Immunodominance in HIV-1–specific Cytotoxic T Lymphocyte Responses in Two Human Histocompatibility Leukocyte Antigens (HLA)-identical Siblings with HLA-A*0201 Are Influenced by Epitope Mutation

Abstract: Primary human immunodeficiency virus (HIV) infection is controlled principally by HIV-specific cytotoxic T lymphocytes (CTL) to a steady-state level of virus load, which strongly influences the ultimate rate of progression to disease. Epitope selection by CTL may be an important determinant of the degree of immune control over the virus. This report describes the CTL responses of two HLA-identical hemophiliac brothers who were exposed to identical batches of Factor VIII and became seropositive within 10 wk of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
122
1
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(136 citation statements)
references
References 43 publications
11
122
1
1
Order By: Relevance
“…Furthermore, the pattern of CTL immunodominance may be influenced by epitope mutations, as shown in human immunodeficiency virus infection. 74 Importantly, the CD8 ϩ cytolytic T-cell response in recovered subjects was not significantly different from the uninfected controls in whom CTL response to HCV-derived peptides has been reported. 7 Along this line, the frequent response to another HLA-A2 restricted CTL epitope within the NS3 region (NS3 1073) in all 3 groups, including healthy seronegative controls, suggested that it may reflect a crossreactive response to an unrelated antigen as well as a response to HCV when analyzed using bulk peptide stimulation.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, the pattern of CTL immunodominance may be influenced by epitope mutations, as shown in human immunodeficiency virus infection. 74 Importantly, the CD8 ϩ cytolytic T-cell response in recovered subjects was not significantly different from the uninfected controls in whom CTL response to HCV-derived peptides has been reported. 7 Along this line, the frequent response to another HLA-A2 restricted CTL epitope within the NS3 region (NS3 1073) in all 3 groups, including healthy seronegative controls, suggested that it may reflect a crossreactive response to an unrelated antigen as well as a response to HCV when analyzed using bulk peptide stimulation.…”
Section: Discussionmentioning
confidence: 95%
“…Hepatitis B virus core peptide was purchased from NeoMPS Inc. (San Diego, CA). The PS-SCL (free N terminus and amidated C terminus) consists of 180 mixtures in an OX 8 …”
Section: Library and Peptide Synthesismentioning
confidence: 99%
“…About 70% of chronically HIV-infected, HLA-A2-positive individuals have circulating CTL that recognize the Gag p17-derived epitope SLYNTVATL (SL9) [8,9]. Although the in vivo effectiveness of SL9-specific CTL has been questioned [8][9][10][11][12], there may at least be a partial benefit from these responses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As one of the more referenced peptides found in literature, FLPSDFF-PSV is known for high affinity binding to A*0201 [46][47][48] as well as for inducing potent CTL responses [49] . Additional controls were the peptides SLYNTVATL and ILKEPVHGV, two other well-studied HIV-derived CTL epitopes [50][51][52] . According to our FP-based classification system, wildtype peptides wt1131 and wt1169 were found to be of high and medium affinity, respectively, matching with the high cytolytic activity level of these CTL clones ( Figure 4B and C).…”
Section: Impact Of Variant Peptides On Mhc Class ⅰ Bindingmentioning
confidence: 99%